Screening of salt tolerant CIP Potato Germplasm for saline areas - Rahman, M.H.; Alam Patwary, M.M.; Barua, H.; Hossain, M.; Hasan, M.M. (Bangladesh Academy of Sciences, 2013)
Fifteen salt tolerant CIP (International Potato Centre) Potato genotypes along with BARI (Bangladesh Agricultural Research Institute) Alu 7 (Diamant) and one local variety viz., Dohazari Sada were evaluated at Bashkhali, Chittagong during 2011-12 to screen the suitable genotypes for cultivation in saline areas of Bangladesh. Diamant and Dohazari Sada and all of the CIP genotypes were found to grow well up to 60 DAP (Days After Planting) at saline areas having healthy plants and no senescence was noticed but after that 61-100% plants died due to high level of soil salinity (6.41dS/m) depending on genotypes. Genotype CIP 112 gave the highest yield (21.07 t/ha) and CIP 102 was comparatively less affected by soil salinity than the other genotypes. However, all the salt tolerant CIP genotypes were found to be promising in the saline soil. DOI: http://dx.doi.org/10.3329/agric.v11i1.15249 The Agriculturists 2013; 11(1) 95-102